Post Memes Seizing the Memes of Production - Bristow, Daniel; Bown, Alfred; Project Muse. (Punctum Books, 2019)
"Art-form, send-up, farce, ironic disarticulation, pastiche, propaganda, trololololol, mode of critique, mode of production, means of politicisation, even of subjectivation - memes are the inner currency of the internet's circulatory system. Independent of any one set value, memes are famously the mode of conveyance for the alt-right, the irony left, and the apoliticos alike, and they are impervious to many economic valuations: the attempts made in co-opting their discourse in advertising and big business have made little headway, and have usually been derailed by retaliative meming. Post-Memes: Seizing the Memes of Production takes advantage of the meme's subversive adaptability and ripeness for a focused, in-depth study. Pulling together the interrogative forces of a raft of thinkers at the forefront of tech theory and media dissection, this collection of essays paves a way to articulating the semiotic fabric of the early 21st century's most prevalent means of content posting, and aims at the very seizing of the memes of production for the imagining and creation of new political horizons. With contributions from Scott and McKenzie Wark, Patricia Reed, Jay Owens, Thomas Hobson and Kaajal Modi, Dominic Pettman, Bogna M. Konior, and Eric Wilson, among others, this essay volume offers the freshest approaches available in the field of memes studies and inaugurates a new kind of writing about the newest manifestations of the written online. The book aims to become the go-to resource for all students and scholars of memes, and will be of the utmost interest to anyone interested in the internet's most viral phenomenon"--
Description based on print version record.
Keywords: Electronic books